Effectiveness of mindfulness based mental fitness training: an impact evaluation study - Pawar, Alhad Anant; Panda, Jayant Kumar; Bobdey, Saurabh (International Journal of Research in Medical Sciences, 2017)
Background: Mindfulness-based mental fitness training (MBMFT) based on Vipassana is a secular, non-religious method found to be useful in reducing stress, anxiety and depression in a variety of population. Studies have revealed that an increasing percentage of population experiences high stress. The present study was conducted to evaluate impact of a mindfulness-based mental fitness training (MBMFT) programme on levels of stress and resilience among students of school in an industrial establishment. Methods: Sixty nine students aged 18-20 years of an industrial establishment who volunteered and met the inclusion criteria were included in the study. The participants were randomly divided into two groups, group I (n=35) were given 8 weeks of Mindfulness-Based Mental Fitness Training, and group II (n=34) followed the normal curricula of the school. Questionnaires were completed on psychological well-being and mindfulness by the participants initially and after 08 weeks. Results: The students who underwent MBMFT (group-I) had significantly (p<0.05) higher FFMQ scores at 08 weeks (130.10±9.69) as compared to baseline scores (122.55±12.7) and scores of the group II (117.95±10.1). Group I students also had lower perceived stress scores at the end of 08 weeks of MBMFT. Personal resilience was assessed only for Group-I using Personal Resilience Questionnaire (PRQ). The PRQ score increased significantly (p= 0.000) from mean baseline score of 157.76±10.14 to 166.31±13.01 at the end of 8 weeks. Conclusions: Mindfulness based Mental Fitness Training is an effective method which can be used to enhance the ability of personnel to combat stress. Future large scale multi centric research is required to further validate the effectiveness of MBMFT and to assess feasibility of inclusion of MBMFT as regular aspect in training institutions.